Role of long-chain acyl-CoAs in the regulation of mycolic acid biosynthesis in mycobacteria - Tsai, Yi Ting (Open Biol, 2017)
One of the dominant features of the biology of Mycobacterium tuberculosis, and other mycobacteria, is the mycobacterial cell envelope with its exceptional complex composition. Mycolic acids are major and very specific components of the cell envelope and play a key role in its architecture and impermeability. Biosynthesis of mycolic acid (MA) precursors requires two types of fatty acid synthases, FAS I and FAS II, which should work in concert in order to keep lipid homeostasis tightly regulated. Both FAS systems are regulated at their transcriptional level by specific regulatory proteins. FasR regulates components of the FAS I system, whereas MabR and FadR regulate components of the FAS II system. In this article, by constructing a tight mabR conditional mutant in Mycobacterium smegmatis mc(2)155, we demonstrated that sub-physiological levels of MabR lead to a downregulation of the fasII genes, inferring that this protein is a transcriptional activator of the FAS II system. In vivo labelling experiments and lipidomic studies carried out in the wild-type and the mabR conditional mutant demonstrated that under conditions of reduced levels of MabR, there is a clear inhibition of biosynthesis of MAs, with a concomitant change in their relative composition, and of other MA-containing molecules. These studies also demonstrated a change in the phospholipid composition of the membrane of the mutant strain, with a significant increase of phosphatidylinositol. Gel shift assays carried out with MabR and PfasII as a probe in the presence of different chain-length acyl-CoAs strongly suggest that molecules longer than C(18) can be sensed by MabR to modulate its affinity for the operator sequences that it recognizes, and in that way switch on or off the MabR-dependent promoter. Finally, we demonstrated the direct role of MabR in the upregulation of the fasII operon genes after isoniazid treatment.